(3GdeHSW aj JaSjQ hJWHjb HfhO eYGjjQ GdeMGSHI GdOhdjI (B:s IAS 2020 - (3Tfha, MeRIs ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2021)
(3eONd Gdi eYGjjQ GdeMGSHI GdOhdjI, eY GdeYjGQ GdeMGSHj GdOhdj Qbe(B1 (3GdPj jJMOK Yf YQV GdbhGFe GdOhdjI hGdeYjGQ GdeMGSHj Qbe (B2 (3GdeJYdb HGdeNRhf, hGdeYjGQ Qbe (B7 (3bGFeI GdJOabGJ GdfbOjI, CeG GdeYjGQ GdKGef GdPj jJVef GdSjGSGJ GdeMGSHjI hGdJZjQGJ aj GdJbOjQGJ hGdCNWGA, hGdeYjGQ GdYGTQ GdPj JVef GdCMOGK HYO aJQI GdJbQjQ hcPdc VQGFH GdONd HGdGVGaI Gdi GdYbGQGJ hGdBdGJ hGdeYOGJ, CeG GdeYjGQ GdJGSY YTQ aJMOK Yf efGaY GdehXajf ceG LGA aj GdeYjGQ Qbe YTQhf GdeMGSHI Yf GdefM GdMchejI hGdGaUGM Yf GdeSGYOGJ GdMchejI, hBKGQ GdJZjQGJ aj CSYGQ UQa GdYedGJ GdCLfHjI ef NdGd GdeYjGQ GdMGOj hGdYTQ, eY JcGdja GdGaJQGV aj GdeYjGQ GdKGdK hGdYTQhf, hGdGaUGMGJ Yf GdCWQGa PGJ GdYdGbI, hcPdc GdeMGSHI hGdJbQjQ ef bHd NWW efGaY GdJbGYO, CeG GdeYjGQ Qbe SHYI hYTQhf hGdeYjGQ GdKGef hGdYTQhf Ydi GdJhGdj aJVefG GdbhGFe GdeGdjI GdefaUdI hGdGSJKeGQGJ aj GdefTBJ GdRejdI hGdeTQhYGJ GdeTJQcI, HGdGVGaI Gdi GdJbQjQ GdeGdj aj GdGbJUGOjGJ PGJ GdJVNe GdLGeM ef NdGd GdeYjGQ Qbe JSYI hYTQhf(B. (3CeG GdeYGjjQ GdKGfj hKdGKhf hGdQGHY hKdGKhf hGdSGOS hKdGKhf aJVefhG GdCOhGJ GdeGdjI(B: (3GdYQV hQHMjI GdSge eY GdJbGQjQ GdeGdjI GdeQMdjI, eY GdgHhW aj bjeI GdCUhd, haj GdGNjQ PcQ dfG GdYbGQGJ GdGSJKeGQjIhGdRQGYI ef NdGd GdeYjGQjf GdCQHYhf hGdMGOj hCQHYhf s
(3GdeQGLY U(B.513- 514s
Keywords: (3GdeMGSHI GdOhdjI(B- (3GdeYGjjQs